Les stratégies de récupération du sportif de haut niveau : focus sur la quantité et la qualité du sommeil - Nédélec, M. (Revue médicale de Liège, 2020)
Elite athletes participate in multiple competitions and are exposed to important training load. There is a need to match the recovery process against such a number of competitions and important training load, with the aim of preventing overtraining and injury. Several recovery strategies exist. Some strategies such as hydration, diet, cold water immersion and sleep are effective in their ability to counteract the fatigue mechanisms. Elite athletes regularly display compromised sleep quantity and quality with sleep quality being most vulnerable prior to major competitive events, during periods of high-intensity training and following long-haul travel to competitions. Compromised sleep quantity and/or quality may be detrimental to the outcome of the recovery process after training and competition. Future studies should focus on the interest of sleep hygiene strategies to optimise recovery, performance and preventing injury.